HUBUNGAN ANTARA KEGIATAN FISIK DAN KESEHATAN MENTAL DI LINGKUNGAN SEKOLAH: KAJIAN LITERATUR TERBARU - Hotmaria Hertawaty Sijabat (Prosiding Seminar Nasional Indonesia, 2025)
This literature review investigates the relationship between physical activity and mental health in the school environment. The review in this study utilized the literature method. The results showed that participation in regular physical activity, whether through physical education, intramural sports or extracurricular activities, can have positive mental health outcomes among students. These benefits include decreased symptoms of anxiety and depression, increased self-esteem and self-confidence, and improved resilience to stress and academic challenges. These findings emphasize the importance of promoting physical activity in schools as a strategy to foster students' mental health and well-being. Recommendations for integrating physical activity into the curriculum and school culture are discussed, with an emphasis on providing a comprehensive physical education program and oflering a variety of sports and fitness activities. By prioritizing physical activity, educational institutions can play an important role in improving students' mental, academic and personal health outcomes.